ANALISIS PENGOLAHAN DATA FORENSIK PADA SOLID STATE DRIVE (SSD) MENGGUNAKAN FRAMEWORK GRR RAPID RESPONSE - Arman Syah Putra; Nurul Aisyah; Safrizal Safrizal (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2022)
The background of this research is to know the data processing on Solid State Drive (SSD) using the GRR Rapid Response framework approach, it will know the data and data processing so that the past data can be known and can be found where the data is, so that it can be used as a reference. Forensic evidence. The problem raised in this research is to try a framework to prove that forensic data can be retrieved and can be used as important data. The method used in this study is to conduct a literature review and conduct trials on Solid State Drives (SSD) using certain methods in order to find out the response of the hard drive in searching data. The purpose and objective of this research is to conduct trials on certain frameworks in conducting forensic data testing. Keywords: Forensic Data, Solid State Drive (SSD), Framework, GGR Rapid Response